2011
DOI: 10.1038/nature10112
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs 103 and 107 regulate insulin sensitivity

Abstract: Defects in insulin signalling are among the most common and earliest defects that predispose an individual to the development of type 2 diabetes. MicroRNAs have been identified as a new class of regulatory molecules that influence many biological functions, including metabolism. However, the direct regulation of insulin sensitivity by microRNAs in vivo has not been demonstrated. Here we show that the expression of microRNAs 103 and 107 (miR-103/107) is upregulated in obese mice. Silencing of miR-103/107 leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
793
3
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 890 publications
(873 citation statements)
references
References 28 publications
42
793
3
12
Order By: Relevance
“…Both miR‐143 and miR‐103 have been described as regulators of glucose homeostasis. Trajkovski et al [2011] demonstrated an up‐regulation of miR‐103 and miR‐107 in obese mice. In addition, the authors showed gain of miR‐103/107 function in liver or fat to result in impaired glucose homeostasis, and identified caveolin‐1 (CAV‐1) as target of these two miRNAs [Trajkovski et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both miR‐143 and miR‐103 have been described as regulators of glucose homeostasis. Trajkovski et al [2011] demonstrated an up‐regulation of miR‐103 and miR‐107 in obese mice. In addition, the authors showed gain of miR‐103/107 function in liver or fat to result in impaired glucose homeostasis, and identified caveolin‐1 (CAV‐1) as target of these two miRNAs [Trajkovski et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Trajkovski et al [2011] demonstrated an up‐regulation of miR‐103 and miR‐107 in obese mice. In addition, the authors showed gain of miR‐103/107 function in liver or fat to result in impaired glucose homeostasis, and identified caveolin‐1 (CAV‐1) as target of these two miRNAs [Trajkovski et al, 2011]. Similarly, conditional over‐expression of miR‐143 in mice has been shown to impair glucose metabolism and insulin‐stimulated AKT activation in the liver of these animals [Jordan et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…1). 105 The inhibition of miR-21, miR-34a, or miR-146a with antisense molecules in b-cells treated with IL-1b improves glucose-induced insulin secretion (Fig. 1).…”
Section: Nct02046395mentioning
confidence: 95%
“…In breast cancer, miR-378* upregulation results in an increase in cell proliferation and lactate production, and a repression of tricarboxylic acid cycle and oxygen consumption, indicating that miR-378* is able to mediate metabolic shift in cancer cells 20 . It has also been reported that hepatic miR-378/378* expression is dysregulated in a rat model of type 2 diabetes and obese mouse models, including genetic ob/ob mice and mice fed a high-fat diet 15,21,22 . However, whether and how miR-378 or miR-378* plays a regulatory role in hepatic glucose and lipid metabolism remains unclear.…”
mentioning
confidence: 98%
“…It has been shown that miRNA could represent another crucial regulatory layer in regulating insulin action 13,14 . miR-103/ 107 and let-7 mainly regulate insulin signalling in peripheral tissues such as adipose tissue and skeletal muscle by targeting caveolin-1 and IR/IRS2, respectively 15,16 . miR-143 and miR-34a affect hepatic insulin signalling by targeting oxysterol-bindingprotein-related protein 8 (ORP8) and Sirtuin 1 (SIRT1), respectively 17,18 .…”
mentioning
confidence: 99%